The Impact of Mean Arterial Pressure and Volume Contraction in With Acute Ischemic Stroke - Bahouth, Mona N.; Saylor, Deanna; Hillis, Argye E.; Gottesman, Rebecca F. (Frontiers in Neurology, 2022)
Background and Purpose Hydration at the time of stroke may impact functional outcomes. We sought to investigate the relationship between blood pressure, hydration status, and stroke severity in patients with acute ischemic stroke (AIS). Methods We evaluated hydration status, determined by blood urea nitrogen (BUN)/creatinine ratio, in consecutive patients with AIS from a single comprehensive stroke center. Baseline mean arterial pressure (MAP) was analyzed using a linear spline with a knot at 90 mmHg. Baseline stroke severity was defined based on admission NIH Stroke Scale scores (NIHSSS) and MRI diffusion-weighted imaging. Results Among 108 eligible subjects, 55 (51%) presented in a volume contracted state. In adjusted models, in the total sample, for every 10 mmHg higher MAP up to 90 mmHg, NIHSSS was 2.8 points lower (p = 0.053), without further statistically significant association between MAP above 90 and NIHSSS. This relationship was entirely driven by the individuals in a volume contracted state: MAP was not associated with NIHSSS in individuals who were euvolemic. For individuals in a volume contracted state, each 10 mmHg higher MAP, up to 90 mmHg, was associated with 6.9 points lower NIHSSS (95% CI −11.1, −2.6). MAP values above 90 mmHg were not related to NIHSSS in either dehydrated or euvolemic patients. Conclusions Lower MAP contributes to more severe stroke in patients who are volume contracted, but not those who are euvolemic, suggesting that hydration status and blood pressure may jointly contribute to the outcome. Hydration status should be considered when setting blood pressure goals for patients with AIS.